Gamification concept for encouraging lecture attendance - Vinothini Kasinathan; Aida Mustapha; Chan Kok Fu; Mohamad Firdaus Che Abdul Rani; Sadesh Manikam (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
New generation of students has high dependence on technology and embrace social learning environments that have low barrier to access. This means in-class lectures are not popular anymore, and in fact has become a burden for them to cope. To resolve the issue of low student attendance, this paper proposes a character growth game with the concept of gamification in education that is able to track and reward student attendance called PetAttendToClass. PetAttendToClass is a client-based system developed using C# and unity3D game engine. Although finding from the UAT session revealed that some users believed that attendance is the responsibility of the student, gamification is meant to turn this mundane responsibility into something motivative, interactive and interesting. It is hoped that by gamifying the class attendance, student will be motivated to attend their daily classes.